Women’s Suppression or Empowerment? A Critical Study of Rubies for a Dog: A Fable - Safyan , Muhammad; Iqbal, Nasar; Nafees, Muhammad; Ramzan, Lubna (Pakistan Journal of Humanities and Social Sciences, 2023)
The purpose of this paper is to investigate the elements of suppression and empowerment of the women in a patriarchal society under critical circumstances. French feminist Simon De Beauvior’s concept of suppression of women is used as a framework for this research for the analysis of Husain’s short story Rubies For a Dog; A Fable. In The Second Sex (1988), she said; Women are not born they are made. In this short story, Husain raises her voice against the suppression of women in the patriarchal society. She gives voice to her female character Samira who fought for the freedom of her innocent father Wazir. She was bound to live in the palace as she is a female. She breaks the rules of patriarchal society and goes to see her father in jail after wearing the clothes of her father. She shaves her head and wears the clothes of her father so that she may look like a man. Her father wishes to have a son and she fights for her father like his son. She rebels against the patriarchal rules and does everything for her father and empowers herself. The deep study of the short story is used as a primary resource and different articles, interviews, magazines and books are also used as secondary resource. The study is significant because it explores the effect of suppression in form of empowerment. Women empower themselves when they are suppressed.